AL IN E- RECRUITMENT- WITH SPECIAL REFERENCE TO PHARMACEUTICAL INDUSTRY - Kumar, Dr. Aakash; Rajasekharan, Dr Bamini; Pavan Sathavalli, Dr. Mahesh; Murthy, Dr. Sharanya (The journal of contemporary issues in business and government, 2022)
Artificial intelligence (AI) is being used very pervasively with the ever-evolving and competitive business world and has become the 21st-century buzzword. Countless innovations in technology have pushed businesses to make their value creation processes more effective and customer friendly. The experimenter was used secondary data where the data was collected from exploration papers, publications, websites, HR blogs, check reports etc. This research would be useful for recruiters and HR managers to consider the fields of AI implementation and management to take advantage of cost-cutting technical developments. Study was made up of job seekers of artificial intelligence in e-recruitment in Pharma industry and primary data collected 200 job seekers from major cities like, Bangalore, Hyderabad, Chennai and Delhi. Study found that there is a relationship between recruitment and Natural language process. The study concluded there is statistically significant relationship between Natural language process, work force and automation variables